Simulasi Perubahan Back Rake Angle Polycrystalline Diamond Carbide Drill Bit untuk Meminimalkan Keausan Pahat - Oegik Soegihardjo; Samuel Trinata (Jurnal Teknik Mesin (Sinta 3), 2020)
The drilling process of an oil well uses a drill bit to drill a hole to drain crude oil from the bowels of the earth to the ground. Tool wear occurs in every cutting or drilling process that uses tool bits. A drill bit is the general term for the tool blade used in the drilling process. Two types of tool bits that are commonly used are roller cone and Polycrystalline Diamond Carbide drill bit or PDC. The case being study is the wear out of the PDC drill bit, that causing unplanned bit trip. This research was conducted as an effort to reduce the wear that occurs on the PDC drill bit. The aim of the research is to simulate the changes of the back rake angle, so that the impact of the back rake angle's changes on the wear of the drill bit could be investigated. The results of the simulations were compared with the tool wear data that occurred at one of the oil drilling locations.